ANALISIS TINGKAT KEPUASAN PASIEN INSTALASI RAWAT INAP KELAS I RUMAH SAKIT UMUM DAERAH (RSUD) BANGKINANG - Supardi Supardi (Jurnal Riset Manajemen Indonesia, 2020)
The purpose of this study was to determine the level of patient satisfaction in the Class I Inpatient Installation of Bangkinang District Hospital. This type of research is quantitative descriptive. The sample of this study was 93 class I inpatient patients obtained through random sampling. Data collection was carried out with 25 items of patient satisfaction expectations questionnaire (α> 306). The analysis conducted is univariate using Importance Performance Analysis (IPA). The results of this study indicate that the average value of satisfaction level is 91.8% where the suitability level of reliability dimensions is 91.5%, responsiveness is 90.0%, assurance is 89.0%, empathy is 97.4% and tangible is 91.1%. Based on the analysis of the Cartesian diagram where of the 25 attributes, there are 1 item in quadrant A, 12 items in quadrant B, 9 items in quadrant C, and 3 items in quadrant D.